Implementasi Model Sistem Penjaminan Mutu Internal (SPMI) di Universitas Islam Bandung - Nan Rahminawati; Asep Dudi Suhardini; Revan Dwi Erlangga (Departement of Mathematics Education, 2024)
Bandung Islamic University (Unisba) as one of the superior accredited private universities has very good and structured SPMI management. This is proven by the recognition from the Director General of Higher Education in August 2017 that Unisba has received an award as a Higher Education Institution that consistently implements a Quality Assurance System in Indonesia at the University level, plus in 2023 based on a survey conducted by UniRank 2023 Bandung Islamic University (Unisba) won 1st place as the best Islamic university in West Java by beating UIN Sunan Gunung Djati which was in 2nd place. Since Unisba received the Superior title for Institutional Accreditation in December 2017, the Higher Education Service Institute (LLDIKTI) has given the task of providing guidance to universities students who still have Good (C) accreditation. With the entire SPMI cycle being implemented well, it is necessary to review the good practices that have been carried out so far, so as to find out what model Unisba has implemented. The method used in carrying out this research is a descriptive analysis method with a qualitative approach. The results of this research show (a) the SPMI implementation process carried out by Unisba has gone through the PPEPP stage well in accordance with the mandate of the law. (b) Unisba's implementation of the SPMI model can be explained well regarding policies, syntax, roles and impacts both directly and indirectly.